Analysis on the Character Design of Asian Indian Cartoon Character Chhota Bheem - Balaji, A. C.; Lakshmikantha, Nandini (Indian Journal of Marketing, 2020)
Chhota Bheem has become a popular Indian animated character on the global stage. He is India’s most successful animation property, with television shows, films, and merchandise. He is a 9-year-old adventurous, bold, and fun-loving boy with astonishing strength. He is one of the fascinating characters among Indian children because of his representation of cultural values, ethics, and positivity. Chhota Bheem is the top-selling animation property in India, including the South Asian markets. Out of Green Gold Animation Studio’s Chhota Bheem franchises, Super Bheem, Mighty Little Bheem, and Baby Bheem are the popular spin-offs. This paper sought to analyze the Asian Indian television animated superhero character "Chhota Bheem" as a character and a brand. This study analyzed the character design with reference to his appearance, body type, shape, colour, and evaluated the character’s appeal as a brand. The research applied semiotic analysis, aimed at analyzing the character’s appeal as a reference to the face of Indian animation character and to improvise the characterization that can have a global identity. The study also examined the media content based on four leading websites such as licenseindia.com, businessstandard. com, financialexpress.com, and brandequity.com. The findings of the study would aid in promoting similar Indian animation properties, thereby motivating animation producers and most importantly, will reduce the dependence of importing animation properties.